Inhibition of Collagenase Q1 of Bacillus cereus as a Novel Antivirulence Strategy for the Treatment of Skin‐Wound Infections. Issue 3 (15th January 2022) - Alhayek, Alaa; Khan, Essak S.; Schönauer, Esther; Däinghaus, Tobias; Shafiei, Roya; Voos, Katrin; Han, Mitchell K. L.; Ducho, Christian; Posselt, Gernot; Wessler, Silja; Brandstetter, Hans; Haupenthal, Jörg; et al.
Abstract: Despite the progress in surgical techniques and antibiotic prophylaxis, opportunistic wound infections with Bacillus cereus remain a public health problem. Secreted toxins are one of the main factors contributing to B. cereus pathogenicity. A promising strategy to treat such infections is to target these toxins and not the bacteria. Although the exoenzymes produced by B. cereus are thoroughly investigated, little is known about the role of B. cereus collagenases in wound infections. In this report, the collagenolytic activity of secreted collagenases (Col) is characterized in the B. cereus culture supernatant (csn) and its isolated recombinantly produced ColQ1 is characterized. The data reveals that ColQ1 causes damage on dermal collagen (COL). This results in gaps in the tissue, which might facilitate the spread of bacteria. The importance of B. cereus collagenases is also demonstrated in disease promotion using two inhibitors. Compound 2 shows high efficacy in peptidolytic, gelatinolytic, and COL degradation assays. It also preserves the fibrillar COLs in skin tissue challenged with ColQ1, as well as the viability of skin cells treated with B. cereus csn. A Galleria mellonella model highlights the significance of collagenase inhibition in vivo. Abstract : Secreted Bacillus collagenases contribute to the bacterial invasion in wound infections by digesting collagen, hence facilitating bacterial and toxin diffusion. The data elucidate that Bacillus collagenases are attractive targets for antivirulence development. Suppressing their activity with small‐molecule inhibitors is an innovative approach to disarm the bacteria without killing them, consequently reducing the bacterial and toxin infiltration and facilitating wound healing.